Delivering on the Sustainable Development Goals through long-term infrastructure planning. (November 2019) - Adshead, Daniel; Thacker, Scott; Fuldauer, Lena I.; Hall, Jim W.
Highlights: The UN SDGs can guide infrastructure practitioners in making informed choices. Infrastructure indicators are directly linked to many SDG target outcomes. Strategic infrastructure interventions can lead to significant SDG progress. Decision-making requires consideration of interdependencies between sectors. Future uncertainties necessitate the assessment of multiple demand scenarios. Abstract: Through the provision of a range of essential services, infrastructure systems profoundly influence development. At a time of increasing global investment in infrastructure, there is a need to support practitioners in making informed choices in order to achieve progress toward sustainable development objectives. Using the 2030 Agenda for Sustainable Development (the SDGs) as a framework to structure infrastructure decision-making and trade-offs, this analysis develops a performance indicator system that assesses the potential development implications of a portfolio of infrastructure investments and policies. We develop metrics to assess the performance of infrastructure-linked targets. We then embed these metrics in a systems model that allows for the quantification of future infrastructure needs and the assessment of portfolios of infrastructure investments and policies that contribute to meeting these needs. These methods are applied to the small-island country of Curaçao, demonstrating the potential for meeting the SDGs through adoption of strategies of cross-sectoral infrastructure investments and policies in the energy, water, wastewater and solid waste sectors. In the face of growing demands for infrastructure services, we find that inaction with regard to infrastructure supply and demand will lead to a 28% decrease in average SDG achievement across these targets by 2030. We assemble a portfolio of interventions that provide infrastructure services across these four sectors that enable achievement of 19 SDG targets directly linked to infrastructure. These interventions imply scaling up of infrastructure where there are gaps in service provision, ranging from an overall 10% increase in the water sector to a 368% increase in waste sector infrastructure from current capacities by 2030. Achieving the SDGs does not necessarily imply more infrastructure: in the energy sector the sustainable policy implies demand reductions of 32% from current levels. Nearly 50% of the assessed targets require intervention in more than one sector, emphasising the interdependent nature of the infrastructure system. The analysis addresses future uncertainties around the key drivers of residential population and tourism growth on the island by modelling infrastructure needs for alternate scenario projections. Averaged across the four sectors, these needs range from −14% (low) to +5% (high) in relation to the moderate projection. The analysis provides the first step towards a practical means of utilising infrastructure to deliver the SDGs, using quantitative indicators to underpin effective decision-making.